Revision of the supposed Triassic, in fact Silurian genus Triadophyllum Weissermel, 1925 (Anthozoa, Rugosa) - D. Weyer (Fossil Record, 2007)
The only existing type specimen of Triadophyllum posthumum Weissermel, 1925 is not a Middle Triassic (middle Anisian, Pelsonian) Scleractinia, but a Silurian Rugosa collected from a Pleistocene erratic boulder of Baltoscandian origin. First serial cross sections demonstrate a synonymy of Triadophyllum Weissermel, 1925 with the worldwide distributed ahermatypic genus Palaeocyathus Foerste, 1888 (including also Enterolasma Simpson, 1900) known from Llandoverian/Wenlockian – Eifelian times. The species Palaeocyathus posthumus as well as the genus are still unknown in the classical Silurian sequences of Gotland and Estonia, which may be the possible origin of the glacial drift. At present, a more precise age determination within the Llandoverian, Wenlockian, or Ludlovian can not be achieved. The nearest certain occurrence of the genus is the early Wenlockian Palaeocyathus conicus (Bul'vanker, 1952) of Podolia (Ukraine), situated likewise on the southwestern margin of the ancient Baltoscandian shield; other records such as the Ludlovian Palaeocyathus bohemicus (Počta, 1902) from the Barrandian (Czech Republic) and Palaeocyathus radiatus (Münster, 1839) from Upper Franconia (Saxothuringia, Germany) are more distant on Gondwana-derived terranes. Das allein existierende Holotypus-Polypar von Triadophyllum posthumum Weissermel, 1925 ist kein Scleractinia-Vertreter der Mittel-Trias (mittleres Anis, Pelson), sondern ein silurisches Rugosa-Taxon, das aus einem Pleistozän-Geschiebe baltoskandischen Ursprungs gesammelt wurde. Eine erste Querschliffserie belegt die Synonymie von Triadophyllum Weissermel, 1925 mit dem weltweit verbreiteten ahermatypischen Genus Palaeocyathus Foerste, 1888 (einschließlich Enterolasma Simpson, 1900), das aus dem Zeitraum Llandovery/Wenlock – Eifel bekannt ist. Die Art Palaeocyathus posthumus und auch das Genus wurden in den klassischen Silur-Schichtfolgen von Gotland und Estland noch nicht gefunden, die als Herkunftsgebiete der glazialen Drift in Betracht kommen. Momentan lässt sich keine präzisere Altersbestimmung innerhalb des Llandovery, Wenlock oder Ludlow erreichen. Das nächste Vorkommen der Gattung, das ebenfalls am SW-Rand des alten Baltoskandischen Schildes liegt, ist Palaeocyathus conicus (Bul'vanker, 1952) im unteren Wenlock von Podolien (Ukraine). Andere Nachweise wie Palaeocyathus bohemicus (Počta, 1902) aus dem Ludlov des Barrandium (Tschechische Republik) und Palaeocyathus radiatus (Münster, 1839) aus dem Ludlow von Oberfranken (Saxothuringikum, Deutschland) gehören zu primär entfernteren Terranes, die von Gondwana herkommen. doi:10.1002/mmng.200700006